An integrative development-in-sociocultural-context model for children's engagement in learning - Wang, Ming-Te; Degol, Jessica L; Henry, Daphne A (The American psychologist, 2019)
The construct of engagement provides a holistic lens for understanding how children interact with learning activities, with distinct behavioral, emotional-affective, and cognitive components forming a multidimensional engagement profile for each child. As the understanding of engagement and recognition of its complexity grow, a pressing need has emerged for a synthetic, coherent review that simultaneously integrates extant literature and clarifies the conceptualization of engagement, identifies its key facilitators and consequences, and proffers a theoretical framework that elaborates on how engagement functions. Using a developmental-contextual approach, this article integrates empirical and theoretical scholarship to illustrate how engagement is produced by developmental and relational processes involving transactions across multiple ecologies. The integrative model of engagement offers a comprehensive perspective on the multiple pathways-psychological, cognitive, social, and cultural-underlying the development of children's engagement. Conceptualizing engagement as a multidimensional construct shaped by interactions between an individual and the environment enriches the field's understanding of the personal, contextual, and sociocultural factors that foster or undermine engagement. This framing also enhances understanding of the psychosocial mechanisms through which learning environments influence engagement. (PsycINFO Database Record (c) 2019 APA, all rights reserved).